1 PENGARUH BELANJA PEGAWAI, MANDATORY SPENDING, DAN PERTUMBUHAN EKONOMI TERHADAP FISCAL SPACE SELURUH PROVINSI DI SUMATERA - aditia Rinaldi Rinaldi (Jurnal Ekonomi Pembangunan, 2018)
Fiscal space is government space to allocate funds for investment and development, the space will be more limited if the proportion of state budget is binding. This study aims to analyze the effect of personnel expenditure, mandatory spending on education, mandatory spending on health, and economic growth to fiscal space in Sumatra during 2011 to 2015. Ordinary least squares (OLS) method were used to gain the data. The data used are panel data, which is a combination of time series and cross-section data. Based on the estimated value, coefficient regression of personnel expenditure is - 0.616776 with confidence level of 95%. It means that every one percent increasing of personnel expenditure, the fiscal space will decrease -0.61 percent, ceteris paribus, coefficient regression value of mandatory spending on education is 0.430530 with confidence level of 95%. It means that every one percent increasing of mandatory spending on education, the fiscal space will increase 0.43 percent, ceteris paribus, coefficient regression of mandatory spending on health is 0.681571 with confidence level of 95%. It means that every one percent increasing of mandatory spending on health, the fiscal space will increase 0.68 percent, ceteris paribus, coefficient regression of economic growth is 1.475030 with confidence level of 95%. It means that every one percent increasing of economic growth, the fiscal space will increase 1.47 percent